Manajemen Pemasaran: Strategi Bersaing - Permatasari, Melinda Dwi (Maliki Interdisciplinary Journal, 2025)
in the era of increasingly high globalization, business development is also growing rapidly and the challenges are also increasing. Where in a business it is necessary to strengthen competitive strategies. In competitive strategies do not bring down opponents but fight in several good ways. Thus in the discussion of this journal explains the meaning of competitive strategy, the threat of competitive strength in a company according to Philip Kotler which has various sub-chapters in the discussion of competitive strategy threats, not only that this journal also explains how to analyze competitors based on several types. The case study in this journal is a cafe in the city of Malang that has been established for a long time continues to adapt to new cafe competitors who implement a modern system so that these old cafes continue to experience extraordinary development. The method used in this study is to use a qualitative method by utilizing existing sources such as previous journals, articles and other reading media.